1995
DOI: 10.1128/aac.39.7.1517
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antifungal activities of DU-6859a, a fluoroquinolone, in combination with amphotericin B and fluconazole against pathogenic fungi

Abstract: DU-6859a is an investigational fluoroquinolone agent with potent bactericidal activity, but by itself it has no antifungal activity. When combined with amphotericin B (AmB), however, DU-6859a clearly enhanced the in vitro antifungal activity of AmB against Candida albicans, Candida tropicalis, Candida krusei, Candida glabrata, and Cryptococcus neoformans in microdilution checkerboard studies. Positive interactions of DU-6859a with AmB against Aspergillus fumigatus were dependent on the medium used; yeast nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…There might be other situations, which are difficult to prove experimentally, in which a poor medium, although it supports fungal growth, acts synergistically with the drug in inhibiting growth, resulting in an appearance of better activity. The discrepancy in the interaction of a fluoroquinolone with amphotericin B against A. fumigatus in YNB (synergistic) and in RPMI (antagonistic) (22), as well as the higher activity of miconazole in richer media (36), could be explained by the growth curves. The high growth in YNB and the poor growth in RPMI correlate with different levels of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There might be other situations, which are difficult to prove experimentally, in which a poor medium, although it supports fungal growth, acts synergistically with the drug in inhibiting growth, resulting in an appearance of better activity. The discrepancy in the interaction of a fluoroquinolone with amphotericin B against A. fumigatus in YNB (synergistic) and in RPMI (antagonistic) (22), as well as the higher activity of miconazole in richer media (36), could be explained by the growth curves. The high growth in YNB and the poor growth in RPMI correlate with different levels of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in MICs for filamentous fungi were also observed when conidia (fungus in the lag phase) and hyphae (fungus in the log or stationary phase) were cultivated in RPMI 1640 (12). In another study where RPMI and YNB were employed the interaction between antimicrobial agents and fungi depended on the type of medium used (22).…”
Section: Discussionmentioning
confidence: 99%
“…The above in vitro observations are supported by limited animal data-synergistic interactions of ciprofloxacin plus fluconazole, ciprofloxacin plus AMB and fluconazole plus ofloxacin in vivo in mice with C. albicans infection are described. 129 However, liposomal AMB and moxifloxacin were not synergistic in a rabbit model of C. albicans endophthalmitis for this species. 130,131 In another study, moxifloxacin protected cyclophosphamide-injected mice against C. albicans bronchopneumonia and reduced mortality rates.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…126 Animal models of invasive aspergillosis have supported the enhanced efficacy of antifungals when combined with fluoroquinolones. 129 Genus-specific differences between Candida and Aspergillus in the interactions of fluoroquinolones with individual antifungals may be related to different affinities of each quinolone for fungal topoisomerases. 127 Determing the clinical relevance (or lack thereof) of these experimental interactions is indicated.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Laboratory work has indicated that inhibition of DNA gyrase is not specific and activity against nonbacterial targets has been shown (Dykstra et al, 1994, Fostel et al, 1996. Nakajima et al, (Nakajima et al, 1995) have reported that quinolone augmented the activity of amphotericin B and fluconazole against a variety of fungi in both in vitro and in vivo assays of combined antifungal activity. Based on theses studies, we aimed to evaluate the antifungal activities of enoxacin and its derivatives against common fungal pathogens; Aspergillus purasiticus, Saccharomyces cervics, Candida albicans and Fusraium solani.…”
Section: Antifungal Activitymentioning
confidence: 99%